Elaboración de un manual de buenas prácticas de manufactura para el proceso de faenamiento de porcinos en el Camal Municipal de Riobamba - Chiliquinga Tapia, Brayan Steven (2021)
The Municipal Camal in Riobamba is a public institution in Chimborazo province, it is dedicated to treat animals for slaughter. The main objective of this research project is to develop a Good Manufacturing Practices Manual for the pork slaughtering line in order to guarantee safety in all stages of production, as well as for its unprocessed meat products and pig carcasses. To prepare the Good Manufacturing Practices Manual, an initial diagnosis was made based on the requirements of Resolution ARCSA-DE-067-2015-GGG and the Organic Law on Agricultural Health, where an initial compliance percentage of 63.72% was obtained. In order to identify the hazards in the pig slaughter line, the HACCP Hazard Analysis and Critical Control Point study was applied, where they are identified and classified according to their hazard category as chemical, physical and biological, and the HACCP Plan was developed, detailing the specific parameters of each Critical Control Point (CCP). With the identification of the CCPs and the initial diagnosis of the non-compliance requirements in the pig slaughter line, three PPROs and 16 prerequisite programs were developed. Therefore, the compliance final situation diagnosis of GMP requirements is 84.96%, obtaining a growth of 21.24% with respect to the initial situation of 63.72%.